A Practical Guide for Pediatric Nuclear Medicine - Bar-Sever, Zvi; Giammarile, Francesco; Israel, Ora; Nadel, Helen (Springer Berlin Heidelberg : Imprint: Springer, 2023)
This open access book will provide a foundation for the understanding of, and knowledge for a successful routine use of diagnostic Nuclear Medicine procedures in children through expertise and cases provided by representative busy pediatric nuclear medicine facilities. The book highlights important aspects of nuclear medicine in children and the differences between adult and pediatric practice where relevant. An introductory chapter provides general information detailing the advantages and limitations for performing nuclear medicine tests in children, as well as suggestions on how to approach and provide relevant data to the patients, their parents or next of kin. In the remaining 11 chapters, containing over 115 cases of children evaluated for various clinical indications, procedures are presented and subsequently detailed according to their clinical significance or prevalence based on the clinical experience of the contributors. The book is organized by organ systems, and also includes a chapter on oncology and infection/ inflammation. Chapters are formatted to provide information regarding clinical indications, preparation including radiopharmaceutical doses and additional medications, study protocol, study interpretation, correlative imaging. Each chapter will include red flags warning and take home messages sections to emphasize important points. The case format is presented with patient history and then study report and impression. Based on practices explored by experts at the forefront of this field, the publication is directed at Nuclear Medicine physicians, radiologists, oncologists and clinicians in various pediatric specialties, medical physicists, medical technologists, radiopharmacists, laboratory medicine scientists and researchers.